Assuring Graduate Capabilities : Evidencing Levels of Achievement for Graduate Employability : Final Report. - Oliver, Beverley (Office for Learning and Teaching, 2015)
Final report of a Teaching Fellowship at Deakin University. This Fellowship set out to work with curriculum leaders to find new ways to assure student achievement of graduate capabilities, with a particular focus on evidencing learning and standards for employability. It sought to define course-wide levels of achievement in key capabilities, articulated in clear statements (originally called standards rubrics, now called Course Learning Outcomes and Standards); implement strategies to evidence student achievement of those standards through student portfolios and course review processes; share the validity, challenges and opportunities of such approaches; and build capacity through a community of practice.